Quality of seedlings of different pepper genotypes grown in millicompost: An organic substrate generated by millipedes' activity - Talita dos Santos Ferreira; Rogério Gomes Pêgo; Luiz Fernando de Sousa Antunes; Maria Fernandes Correia; Rosária da Costa Faria Martins; Margarida Goréte Ferreira do Carmo (International Journal of Recycling of Organic Waste in Agriculture, 2022)
Purpose To evaluate the production and the quality of seedlings of different pepper genotypes produced on millicompost as an organic substrate.Method Three experiments were carried out, one for each pepper genotype (ENAS-5007, ENAS-5031 and ENAS-5032) in which three substrates were evaluated: 100% Millicompost (S1); Millicompost MIX (50% millicompost + 50% powdered coconut fiber) (S2) and Carolina organic® commercial substrate (S3). Variables evaluated: shoot and root dry mass (SDM and RDM), number of leaves (NL), plant height (PH), seedling vigor (SV) and clod stability (CS). The data were subjected to the analysis of variance and the means were compared by the Tukey’s test at 5% probability level.Results For the ENAS-5007 and ENAS-5032 genotypes, there was a significant difference in all the variables analyzed, being S1 and S3 the substrates with the highest and the lowest performances, respectively. In the ENAS-5031 genotype, SDM and RDM did not differ between S1 and S2. For ENAS-5031, there were significant differences in PH, NL and SV, in which S1 promoted the best results; however, no significant difference was observed for CS.Conclusion The 100% millicompost substrate promoted the best development of pepper seedlings in all the three genotypes evaluated. However, the combination of the millicompost MIX has the potential to be used, as it promotes seedlings of superior quality in comparison to the commercial substrate, maximizing the use of millicompost as a substrate for the production of organic pepper seedlings.